1987
DOI: 10.1042/bj2460241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on tissue glucose utilization in conscious resting rats. Major glucose-sparing effect in working muscles

Abstract: The effects of fasting on glucose metabolism in the conscious resting rat were studied. Fasting decreased whole-body glucose utilization by 40%. The fast induced a decrease in glucose utilization in muscles which are constantly working even in the resting state, i.e. heart, diaphragm and postural muscles. No modification was observed in other tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 24 publications
(26 reference statements)
6
84
1
Order By: Relevance
“…Data were normalized (%) against control state (non-fasted, non-diabetic conditions) and graphed as a function of total blood ketone bodies level (mmol/L). The study, method, and reported outcome is noted for each point: (a) data from Al-Mudallal et al, 21 ketosis by KG diet in rat, 2-DG method; no significant cortical change in CMR glc , (b) data from Corddry et al, 22 3 days fasted rats, 2-DG method; frontal cortical change, not significant, (c) and (d) data from Dalquist et al, 27 3 days fasted rats, A-V uptake method; no significant change, (e) data from Hasselbach et al, 5 3.5 days fasted humans, PET-FDG imaging; significant reduction, (f ) data from Owen et al, 1 5 to 6 weeks fasted obese human subjects, A-V uptake method, CMR glc , was indirectly calculated by O 2 consumption; significant change, (g) data from Redies et al, 2 20 to 24 days fasted obese human subjects, PET-FDG and A-V uptake method; significant CMR glc reduction, (h) data from Ruderman et al, 7 1-2 days fasted rats, A-V uptake method; trended significant, (i) Data from Mans et al, 6 2 days fasted rats, compartmental modeling with non-trapping tracer (autoradiography); significant reduction, (j) data from Issad et al, 28 2 days fasted rats, (autoradiography), no significant change, (k) data from Cherel et al, 3 6 days fasted rats, modified 2-DG method, no significant change. The meta-analysis plot shows a linear relationship between CMR glc and level of ketosis in human or rat subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Data were normalized (%) against control state (non-fasted, non-diabetic conditions) and graphed as a function of total blood ketone bodies level (mmol/L). The study, method, and reported outcome is noted for each point: (a) data from Al-Mudallal et al, 21 ketosis by KG diet in rat, 2-DG method; no significant cortical change in CMR glc , (b) data from Corddry et al, 22 3 days fasted rats, 2-DG method; frontal cortical change, not significant, (c) and (d) data from Dalquist et al, 27 3 days fasted rats, A-V uptake method; no significant change, (e) data from Hasselbach et al, 5 3.5 days fasted humans, PET-FDG imaging; significant reduction, (f ) data from Owen et al, 1 5 to 6 weeks fasted obese human subjects, A-V uptake method, CMR glc , was indirectly calculated by O 2 consumption; significant change, (g) data from Redies et al, 2 20 to 24 days fasted obese human subjects, PET-FDG and A-V uptake method; significant CMR glc reduction, (h) data from Ruderman et al, 7 1-2 days fasted rats, A-V uptake method; trended significant, (i) Data from Mans et al, 6 2 days fasted rats, compartmental modeling with non-trapping tracer (autoradiography); significant reduction, (j) data from Issad et al, 28 2 days fasted rats, (autoradiography), no significant change, (k) data from Cherel et al, 3 6 days fasted rats, modified 2-DG method, no significant change. The meta-analysis plot shows a linear relationship between CMR glc and level of ketosis in human or rat subjects.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation, 800 pl of each supernatant was added to 10 ml scintillation cocktail (Beckman Ready Value) and the radioactivity determined (Beckman LS6000). Tissue glucose utilization index (GUI) was calculated as described by Issad et al (1987) by dividing the radioactivity (d.p.m.) of 2DG-6-phosphate in the tissues by the calculated 60 min integral of the ratio of blood 2DG/blood glucose (d.p.m.…”
Section: Introductionmentioning
confidence: 99%
“…ng' ). As in Issad et al (1987), the value obtained was not corrected by the discrimination factor for 2-deoxy-glucose in metabolic pathways (see Ferre et al, 1985 …”
Section: Introductionmentioning
confidence: 99%
“…[4]). The glucose-sparing effect of lipid-derived fuels has been demonstrated in working muscles in starvation [5,6], and can be reproduced in perfused hearts from fed rats by the provision of ketone bodies or acetate [1][2][3][4][5][6][7]. PDH is inactivated [1], and specific inhibition of PFK-1 has been demonstrated by measurements of the detritiation of [3-3H]glucose [7].…”
Section: Introductionmentioning
confidence: 99%